Rigged Elections: The Failure of Mexico’s New Labor Model to Protect Farmworker Rights - Daria, James (Frontera Norte, 2023)
Due to recent labor reforms and the United States-Mexico-Canada Agreement (USMCA) negotiation, Mexico ratified freedom of association and collective bargaining rights. This new labor model promises the end of employer protection unions that thwart labor organizing and drive down wages. Through an ethnographic case study of farm labor organizing in the agro-export industry in San Quintín, Baja California, Mexico, this article argues that recent labor reforms are not sufficient to democratize labor relations in rural industries as they fail to overcome regional and transnational power structures. Although limited to one case, this article fills a gap in the literature on the impact of recent labor reforms on farmworkers. Mexico’s salaried agricultural workers offer critical insights into the promises and failures of current efforts to reform labor laws and remediate the adverse effects of economic integration.